Kepastian Hukum Alasan Kemanusiaan sebagai Dasar Pertimbangan Para Pihak dalam Melakukan Restorative Justice - Nashwa Nawra Rahardja; Christin Septina Basani (Jurnal Hukum Lex Generalis, 2025)
The implementation of restorative justice in Indonesia faces significant challenges in maintaining legal certainty, particularly when humanitarian grounds are used as the basis for terminating prosecution. In practice, law enforcement officers often consider the offender’s socio-economic conditions, health, and vulnerability as reasons for applying restorative justice, even when the formal requirements stipulated in legislation are not fully met. In addition to a statutory and conceptual approach and case studies, this study uses a normative juridical method by examining pertinent laws and regulations, including Law Number 11 of 2021 on the Prosecutor's Office, the Attorney General's Regulation Number 15 of 2020, the Chief of Police Regulation Number 8 of 2021, and the Supreme Court Regulation Number 1 of 2024. The findings reveal that humanitarian considerations can serve as a legitimate basis for terminating prosecution to achieve substantive justice. However, this flexibility risks creating disparities if not more clearly regulated. Therefore, more detailed and uniform guidelines are needed to ensure that the application of restorative justice on humanitarian grounds remains consistent with the principles of legal certainty, human rights protection, justice values, and the concept of progressive law that places human welfare above rigid legal formalities.